Strategies for rice self-sufficiency in Côte d’Ivoire - Dagnogo, Foussata (European Journal of Applied Sciences, 2021)
Côte d’Ivoire is a country which is not self-sufficient in rice despite its combined agricultural potential. It is timely to make an analysis of the problems encountered by the actors of the value chain to make concrete proposals to meet the challenge of self-sufficiency in rice in the country. Thus, documentary research and a survey were carried out on producers. It appeared that the actors in the rice production system (rice farmers, processors, traders) encountered some difficulties which do not allow for a match between local demand and local rice production. This situation results from the inability of suppliers to differentiate and qualify their products to meet the requirements of Ivorian rice consumers. Faced with such a situation of failure, the public authorities can help by supporting the organization of the actors in the rice production system through an association that enables them to mobilize and activate all local resources to serve their activities. Public actions are insufficient and centralized. Thus, there is a need for decentralized structures in Côte d’Ivoire, particularly around local authorities, to act in synergy and with the support of local private producers.